Thinking in a different language: the Orientalist Senkovskii and ‘Orientalism’ - Serikoff, Nikolaj (Acta Orientalia Vilnensia, 2009)
The Wellcome Library, London, Institute of Oriental Studies, MoscowThis article deals with the research methods of an alumnus of the University of Wilno, the controversial Russian Orientalist Osip Ivanovich Senkovskii (1800–1859). His attitude towards the scholarly and literary production of his contemporaries—the Austrian Orientalist von Hammer-Purgstall, Russian historian Karamzin, and Russian poet Zhukovskii—is reflected in his letters to his teacher Joachim Lelewel. Senkovskii, at the time considered even a ‘literary clown’ in his popular writings, criticised the leading Western theories of Eastern culture. His views about the necessity to learn the East from inside as opposed to the theories of the European Orientalists found support only 150 years later in the works of the Palestinian scholar Edward W. Said (1935–2003).